Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12983-019-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression vs. sequence divergence: comparative transcriptome sequencing among natural Rhinolophus ferrumequinum populations with different acoustic phenotypes

Abstract: Background Although the sensory drive hypothesis can explain the geographic variation in echolocation frequencies of some bat species, the molecular mechanisms underlying this phenomenon are still unclear. The three lineages of greater horseshoe bat (Rhinolophus ferrumequinum) in China (northeast, central-east, and southwest) have significant geographic variation in resting frequencies (RF) of echolocation calls. Because their cochleae have an acoustic fovea that is highly sensitive to a narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 100 publications
0
21
2
Order By: Relevance
“…Results from these studies and, more recently, genome-wide screens have revealed that multiple hearing genes show molecular adaptation in lineages of echolocators, in some cases involving convergent amino acid replacements [20][21][22][23][24]. Despite insights from such comparative sequencing studies, little is known about the genetic basis of divergence in echolocation call frequencies among populations and closely related species of bats, including the role of gene expression difference (but see [25]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from these studies and, more recently, genome-wide screens have revealed that multiple hearing genes show molecular adaptation in lineages of echolocators, in some cases involving convergent amino acid replacements [20][21][22][23][24]. Despite insights from such comparative sequencing studies, little is known about the genetic basis of divergence in echolocation call frequencies among populations and closely related species of bats, including the role of gene expression difference (but see [25]).…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,23,36]). At the intra-specific level, Zhao et al [25] were the first to study the genetic basis of variation in echolocation call frequencies in three geographical populations of the greater horseshoe bat (R. ferrumequinum) using comparative transcriptome sequencing. However, in this study, variation of call frequencies among the focal populations was slight (less than 8 kHz), potentially limiting the sensitivity of such an approach for distinguishing true candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of gene expression and alternative mRNA splicing are two major forms of transcriptional regulation, responsible for the origin of novel phenotype and phenotypic diversity 4 7 . Recently, high-throughput transcriptome sequencing (RNA-seq) of cochlear tissue has been used to uncover differentially expressed genes possibly associated with the origin of ultrahigh frequency hearing 8 , the divergence of different echolocating types 9 and echolocation call frequency variation 10 . In these earlier studies, the reference used for quantification of gene expression was from a de novo assembly based on the short RNA-seq reads which may contain many artificial transcripts 11 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The current FL transcriptomes generated in this study are sufficient to be reused in the several aspects. They can be used as the reference to reanalyze the RNA-seq datasets of cochlea in previous comparative transcriptomic studies 8 10 . Quantification of transcript expression by mapping reads to the FL transcriptome will help to improve the accuracy of identifying differentially expressed transcripts 12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…On the other hand, driven by declining costs, RNA-seq is becoming increasingly accessible to labs with modest resources; and as a result, it is being employed on an everexpanding catalog of non-model organisms, pervading the fields of agriculture, aquaculture, ecology, and environment. A very short list of recent studies include: environmental stress response in sea-trout [3], coral [4], ryegrass [5], pigeonpea [6], tiger barb [7]; immune response to parasites and pathogens in guppy [8], eel [9], silkworm [10], peanut [11], sunflower [12]; mechanisms of phenotypic divergence in hares [13], bats [14], grass carps [15]; effect of diet in the growth and development in shrimp [16], yellow perch [17], mandarin fish [18], grenadier anchovy [19], catfish [20], tilapia [21], bass [22]. It is only likely that RNA-seq will continue to rapidly proliferate while high-quality reference databases grow at a slow pace.…”
Section: Introductionmentioning
confidence: 99%